DEVELOPING CLASROOM ACTION RESEARCH (CAR) TRAINING MODEL BASED ON MENTORING TO IMPROVE SENIOR HIGH SCHOOL MATHEMATICS TEACHERS’ PROFESSIONALISM IN BREBES (Universitas Negeri Semarang, 2015)
Classroom-based action research (CAR) for high school math teachers is very important to develop their professionalism. To improve the competence of teachers, a development of CAR training model based on mentoring is needed. This study aims to produce an appropriate CAR training model based on mentoring to improve teachers’ professionalism. This study employed research and development (R & D) model. The product development stages are, (a) training manuals and instructor guidelines; (B) material guidebook and module for participants; and (c) CARtraining model. The technique of collecting data used interviews, documentation, observation, and questionnaires. The model validation was done by experts and practitioners. Test models included limited trial on 16 teachers and the trial was expanded to 24 high school math teachers in Brebes Regency. The result shows that: (1) the productwhich is validated by experts and practitioners obtains a mean score of 62.15 (good), (2) the final training model is very feasible to be used by the indication of the its mean score at 3.59 (very high) for its usefulness, themean score of 3.48 (very high) for its practicality, the mean score of 3.58 (very high) for its feasibility. The implementation of training program is also capable of producing CARresearch reports. The conclusions of research is that the final model of CAR training based on mentoring and its training instruments are very feasible to be used to improve the professionalism of senior high school math teachers in Brebes.